Bile Salt Hydrolase of Bifidobacterium longum—Biochemical and Genetic Characterization - Tanaka, Hiroshi (American Society for Microbiology, 2000)
A bile salt hydrolase (BSH) was isolated from Bifidobacterium longum SBT2928, purified, and characterized. Furthermore, we describe for the first time cloning and analysis of the gene encoding BSH (bsh) in a member of the genus Bifidobacterium. The enzyme has a native molecular weight of 125,000 to 130,000 and a subunit molecular weight of 35,024, as determined from the deduced amino acid sequence, indicating that the enzyme is a tetramer. The pH optimum of B. longum BSH is between 5 and 7, and the temperature optimum is 40°C. The enzyme is strongly inhibited by thiol enzyme inhibitors, indicating that a Cys residue is likely to be involved in the catalytic reaction. The BSH of B. longum can hydrolyze all six major human bile salts and at least two animal bile salts. A slight preference for glycine-conjugated bile acids was detected based on both the specificity and the K(m) values. The nucleotide sequence of bsh was determined and used for homology studies, transcript analysis, and construction and analysis of various mutants. The levels of homology with BSH of other bacteria and with penicillin V acylase (PVA) of Bacillus sphaericus were high. On the basis of the similarity of BSH and PVA, whose crystal structure has been elucidated, BSH can be classified as an N-terminal nucleophile hydrolase with Cys as the N-terminal amino acid. This classification was confirmed by the fact that a Cys1Ala exchange by site-directed mutagenesis resulted in an inactive protein. Reverse transcription-PCR experiments revealed that bsh is part of an operon containing at least two genes, bsh and glnE (GlnE is glutamine synthetase adenylyltransferase). Two UV-induced BSH-negative mutants and one spontaneous BSH-negative mutant were isolated from B. longum SBT2928 cultures and characterized. These mutants had point mutations that inactivated bsh by premature termination, frameshift, or amino acid exchange.